Missing in action: practice, paralegality, and the nature of immigration enforcement. Issue 5 (4th July 2017) - Valdez, Inés; Coleman, Mat; Akbar, Amna
Abstract: U.S. immigration control is typically understood in terms of enforcement practices undertaken by federal officers guided by legislation and court decisions. While legislation and court opinions are important components of the immigration control apparatus, they do not adequately account for immigration control 'on the ground.' To explore this problem, we advance the concept of paralegality, the practices and operations that constitute a dynamic system of actions and relationships that are not simply linear applications of legislation or judicial decisions but may in fact extend or counter these texts. We illustrate the importance of paralegality by reconstructing the evolution of the §287(g) and Secure Communities programs, both of which have shape-shifted dramatically since their inception. Our account of immigration control highlights the problem practice poses for law, proposes a theoretical alternative to textual-law-centric research on immigration and law enforcement, and contributes to scholarship on everyday citizenship.